The Role of Parenting Stress in Young Children's Mental Health Functioning After Exposure to Family Violence. Issue 5 (13th September 2013) - Roberts, Yvonne Humenay; Campbell, Christina A.; Ferguson, Monette; Crusto, Cindy A.
<x xml:space="preserve">Abstract</x> This study evaluates the associations of young children's exposure to family violence events, parenting stress, and children's mental health functioning. Caregivers provided data for 188 children ages 3 to 5 years attending Head Start programming. Caregivers reported 75% of children had experienced at least 1 type of trauma event, and 27% of children had experienced a family violence event. Child mental health functioning was significantly associated with family violence exposure after controlling for children's age, gender, household income, and other trauma exposure (β = .14, p = .033). Stress in the parenting role partially mediated the relationship between family violence exposure and young children's mental health functioning (β = .12, p = .015, 95% confidence interval [0.02, 0.21]). Interventions for young children exposed to family violence should address the needs of the child, as well as the caregiver while also building healthy parent–child relationships to facilitate positive outcomes in children faced with trauma.